SISTEM PENDUKUNG KEPUTUSAN KATEGORI RUMAH TIDAK LAYAK HUNI DI KELURAHAN MAJIDI SELONG KABUPATEN LOMBOK TIMUR DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Marwan Hakim (Universitas Bumigora, 2017)
Decision Support System (DSS) is an interactive information system that provides information, modeling, and data manipulation. This system is used to assist in decision-making processes in semi-structured situations of unstructured situations, in which no one knows uncertainly how decisions should be made. Application of Simple Additive Weighting (SAW) Method with the final result shown in the ranking of the weighting process based on the criteria and sub criteria. Habitable home category can be directly seen from the value and ranking so that it can be determined whether or not the people get help, whether in the form of home renovation or home surgery. With this application is expected all problems to the determination of the category of for the poor wrong target will be solved and no more people complain about this, and for the government is expected to convey the mandate that is correct and no errors